Non-alcoholic Steatohepatitis Pathogenesis, Diagnosis, and Treatment - Zhu, Bo; Chan, Siu-Lung; Li, Jack; Li, Kathryn; Wu, Hao; Cui, Kui; Chen, Hong (Frontiers in Cardiovascular Medicine, 2021)
There has been a rise in the prevalence of nonalcohol fatty liver disease (NAFLD) due to the popularity of western diets and sedentary lifestyles. One quarter of NAFLD patients will be diagnosed with non-alcoholic steatohepatitis (NASH), with histological evidence not only of fat accumulation in hepatocytes but also of liver cell injury and death due to long term inflammation. Severe NASH patients have increased risks of cirrhosis and liver cancer. In this review, we discuss the pathogenesis and current diagnosis for NASH, and current drug development for this life-threatening liver disease.